CAUSES OF ORTHODONTIC TREATMENT RELAPSE - Aprilia, Tasya; Nabilahsari, Thasia Putri; Fransisca, Tiara; Pakpahan, Evie Lamtiur (Moestopo International Review on Social, Humanities, and Sciences, 2025)
Orthodontic treatment is one type of treatment performed in the field of dentistry aimed at regulating the arrangement of the teeth. Relapse is the movement of teeth back to their original position after orthodontic treatment. Relapse in orthodontic treatment is a complex problem with many factors potentially affecting the treatment outcome. The detailed causes of relapse are not yet known, but there are several factors that can affect the periodontal ligament, alveolar bone, facial structure growth, soft tissue pressure and interdigitates. In addition to previously mentioned factors, tongue thrust, mouth breathing, nail biting, and bad lip habits could lead to relapse of orthodontics treatment. However, relapse can be prevented by good retention of the teeth to stabilize the correction. Objective: To explain the causes of relapse in orthodontic treatment. Methods: Databases, such as PubMed and Google Scholar, were used as primary source of information. Included literatures were ranged from 2012 to 2024, written in English or Bahasa, and has publicly available full article version. Results: A total of 22 references were found and relevant to the topic of causes of relapse in orthodontic treatment. Conclusion: In conclusion, relapse of orthodontic treatment was caused by various factors including periodontal ligament, alveolar bone, facial structure growth, soft tissue pressure and interdigitation. In addition, tongue thrust, mouth breathing, nail biting and lip habits were also considered as compounding factors of orthodontic treatment relapse.